2022
DOI: 10.1149/2162-8777/ac8371
|View full text |Cite
|
Sign up to set email alerts
|

Material Removal Rate Prediction for Sapphire Double-Sided CMP Based on RSM-SVM

Abstract: As a crucial substrate material for optoelectronic materials, sapphire has important applications in both military and civilian fields. In order to achieve the final processing quality of sapphire substrate materials, double-sided chemical mechanical polishing (DS-CMP) is a necessary process, which is also a guarantee for the preparation of high-end LED chips. Here, the sapphire DS-CMP processing plan based on the Box-Behnken design is obtained and experimented, then a hybrid approach of response surface metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Single-crystal sapphire specimen (α-Al 2 O 3 ) are currently one of the most widely applied materials in the fields of defense, aerospace, microelectronics, and the medical domain [ 1 , 2 , 3 , 4 ] due to their excellent physicochemical properties and material characteristics, such as high hardness (Mohs hardness 9), high melting point (2045 °C), high light transmittance, high chemical stability, and high thermal stability [ 5 , 6 , 7 , 8 , 9 , 10 ]. Sapphire has not only become the most widely used substrate material for traditional LEDs [ 11 , 12 , 13 , 14 ] but also has a large number of applications in mini/micro-LEDs, which are currently very popular.…”
Section: Introductionmentioning
confidence: 99%
“…Single-crystal sapphire specimen (α-Al 2 O 3 ) are currently one of the most widely applied materials in the fields of defense, aerospace, microelectronics, and the medical domain [ 1 , 2 , 3 , 4 ] due to their excellent physicochemical properties and material characteristics, such as high hardness (Mohs hardness 9), high melting point (2045 °C), high light transmittance, high chemical stability, and high thermal stability [ 5 , 6 , 7 , 8 , 9 , 10 ]. Sapphire has not only become the most widely used substrate material for traditional LEDs [ 11 , 12 , 13 , 14 ] but also has a large number of applications in mini/micro-LEDs, which are currently very popular.…”
Section: Introductionmentioning
confidence: 99%
“…Double-sided polishing technology is the preferred method for processing sapphire wafers [ 6 ]. Many scholars have conducted research on the double-sided CMP processing of sapphire wafers.…”
Section: Introductionmentioning
confidence: 99%
“…Wang demonstrated a method of trajectory in double-side autonomous grinding considering the dynamic friction coefficient [ 12 ]. Deng et al revealed the influence of polishing process parameters on the surface quality of sapphire [ 13 ] and then obtained and experimented on the sapphire DS-CMP processing plan based on the Box–Behnken design [ 6 ], given the optimal process parameter combinations, and obtained the maximum MRR of 387.59 nm min −1 . Satake, based on the pressure distribution control, proposed an analytical model of the removal distribution [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under normal circumstances, what we call CMP refers to the single-sided CMP, that is, only one side of the sapphire is polished. However, single-sided CMP usually has the problem of a low polishing rate, so some researchers have proposed the introduction of double-sided CMP into the sapphire CMP process, and it has been proved that the working efficiency of double-sided CMP is higher than that of single-sided CMP [138,139]. For instance, Li et al explored the working efficiency of dual-sided CMP of sapphire, and the results showed that the MRR and Ra of dual-sided sapphire CMP were significantly superior to that of single-sided CMP under the same parameters (Figure 13C) [139].…”
Section: Introducing Other Polishing Processesmentioning
confidence: 99%